2014
DOI: 10.1097/qai.0b013e3182a1bca4
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Modification of FOXP3 in Patients With Chronic HIV Infection

Abstract: Objectives Human immunodeficiency virus type 1 (HIV-1) modulates host cell epigenetic machinery to control its own replication and induce immune suppression. HIV-1 infection leads to activation of T regulatory cell (Treg), but the mechanism underlying this immune modulation is unclear. Treg plays a prominent role in gut-mucosal immune tolerance by restraining excessive effector T-cell responses, a mechanism that is known to be disturbed in chronic HIV-1 infection. DNA methylation plays a major role in Treg lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 41 publications
0
25
0
Order By: Relevance
“…For example, Abdel-Hameed, et al recently reported that chronic HIV infection is associated with alterations in expression of methylation machinery including suppression of DNMT-1 activity, leading to increased FoxP3 promoter demethylation (60). However, others have demonstrated that HIV may enhance the activity of DNMTs, leading to hypermethylation and inactivation of genes important for anti-viral function, such as IFNγ (61).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Abdel-Hameed, et al recently reported that chronic HIV infection is associated with alterations in expression of methylation machinery including suppression of DNMT-1 activity, leading to increased FoxP3 promoter demethylation (60). However, others have demonstrated that HIV may enhance the activity of DNMTs, leading to hypermethylation and inactivation of genes important for anti-viral function, such as IFNγ (61).…”
Section: Discussionmentioning
confidence: 99%
“…The HIV-1-induced epigenetic modulations were also demonstrated in the CD4 + FoxP3 + regulatory T cells (Treg) [ 14 ]. Recent study showed that Treg cells suffered demethylation in the FOXP3 promoter after HIV-1 infection.…”
Section: Introductionmentioning
confidence: 99%
“…Recent study showed that Treg cells suffered demethylation in the FOXP3 promoter after HIV-1 infection. Furthermore, an elevated frequency of Treg cells was found in the gut mucosa of HIV-1 infected patients due to possible aberrant methylation processes [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The same group found the CpG sites in the Foxp3 locus to be hypermethylated due to increased expression of DNMT3b [ 105 ]. Another report, however, showed increased frequency of Treg cells in the gut mucosa of HIV-1 infected patients due to decreased methylation of Foxp3 promoters in the gut associated T cells, causing the induction of iTreg cells [ 160 ]. They also reported that the Foxp3 promoter was significantly de-methylated possibly due to the downregulation of key DNMT enzymes in HIV patients when compared to uninfected control subjects [ 160 ].…”
Section: Epigenetic Modulation Of Immune Cells As a Results Of Hiv mentioning
confidence: 99%